Industrial production of organophosphate flame retardants (OPFRs): big knowledge gaps need to be filled? - Huang, Jianan (2022)
Since the phase-out of traditional halogenated flame retardants (HFRs), interests of research are gradually being shifted to organophosphate flame retardants (OPFRs), and this can be reflected by the increasing number of publications on OPFRs year by year. Here, an extensive survey is conducted in an attempt to generate a list of OPFRs that are being produced in factories, and to investigate the annual production volume (APV). This survey suggests that at least n = 56 OPFR monomers and n = 62 OPFR mixtures are being currently produced in 367 factories around the world, and 201 out of them are in Mainland China. APV of OPFRs was estimated as 598,422 metric tons, and this number could be underestimated due to the limitation of available information. We also notice that current researches are confined to a limited number of OPFRs, especially for OP esters (OPEs), and other OPFRs with different structures from OPEs has been rarely studied. Based on all the collected datasets, we provide five recommendations for how to proceed with future research to more comprehensively understand the currently-produced OPFRs in the environment.